Serum Uric Acid, Alzheimer-Related Brain Changes, and Cognitive Impairment - Kim, Jee Wook; Byun, Min Soo; Yi, Dahyun; Lee, Jun Ho; Jeon, So Yeon; Ko, Kang; Jung, Gijung; Lee, Han Na; Lee, Jun-Young; Sohn, Chul-Ho; Lee, Yun-Sang; Shin, Seong A; et al. (Frontiers in Aging Neuroscience, 2020)
Background: Despite known associations of serum uric acid (UA) with Alzheimer’s disease (AD) dementia or cognitive impairment, the underlying neuropathological links were poorly understood. We aimed to examine the relationships of serum UA with in vivo AD pathologies including cerebral beta-amyloid (Abeta) and tau deposition, AD-signature region cerebral glucose metabolism (AD-CM), and white matter hyperintensities (WMH). We also investigated the association between serum UA and cognitive performance, and then assessed whether such an association is mediated by the brain pathologies. Methods: A total of 430 non-demented older adults underwent comprehensive clinical assessments, measurement of serum UA level, and multimodal brain imaging, including Pittsburgh compound B-positron emission tomography (PET), AV-1451 PET, fluorodeoxyglucose (FDG)-PET, and magnetic resonance imaging scans. Mini-Mental State Examination (MMSE) and word list recall (WLR) test scores were used to measure cognitive performance. Results: Serum UA level was significantly associated with AD-CM, but not with Abeta deposition, tau deposition, or WMH volume. Serum UA levels also had significant association with WLR and marginal association with MMSE; such associations disappeared when AD-CM was controlled as a covariate, indicating that AD-CM has a mediating effect. Conclusion: Higher serum UA may protect against AD-related cognitive decline by preserving AD-related regional brain metabolism.